2021
DOI: 10.1093/milmed/usab117
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Use in Operation Enduring Freedom

Abstract: Introduction Ketamine is a dissociative anesthetic increasingly used in the prehospital and battlefield environment. As an analgesic, it has been shown to have comparable effects to opioids. In 2012, the Defense Health Board advised the Joint Trauma System to update the Tactical Combat Casualty Care Guidelines to include ketamine as an acceptable first line agent for pain control on the battlefield. The goal of this study was to investigate trends in the use of ketamine during Operation Endur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Ketamine use in the US military was established in a 2012 Tactical Combat Casualty Care (TCCC) memorandum and formalised in the 2014 TCCC update. Prior studies have demonstrated increased ketamine usage rates by military medical personnel following updates of TCCC guidelines but only one previous small study has sought to evaluate the subsequent effect on opioid use 18 19. This study aimed to assess the effect of ketamine adoption on opioid usage in all US combat operations over a 10-year period and to demonstrate an opioid-sparing effect of ketamine protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine use in the US military was established in a 2012 Tactical Combat Casualty Care (TCCC) memorandum and formalised in the 2014 TCCC update. Prior studies have demonstrated increased ketamine usage rates by military medical personnel following updates of TCCC guidelines but only one previous small study has sought to evaluate the subsequent effect on opioid use 18 19. This study aimed to assess the effect of ketamine adoption on opioid usage in all US combat operations over a 10-year period and to demonstrate an opioid-sparing effect of ketamine protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine, a multimodal dissociative anesthetic, is a common analgesic administered to combat-wounded service members in a forward-deployed setting [ 23 , 24 , 25 ]. It is used as a trauma analgesic and anesthetic alone or in conjunction with opioids [ 26 ] because it preserves respiration and hemodynamic stability after injury [ 23 , 27 ].…”
Section: Introductionmentioning
confidence: 99%